Functional Behaviour of Materials, Liquid Crystals - Elliot James A.; Reimer Leila; Harrison Richard; CORE-Materials
Este conjunto de animaciones muestra diversos comportamientos que exhiben los cristales lq̕uidos. Contiene los siguientes elementos:Birefringence in liquid crystals Nematic liquid crystal through an optical microscope Linear polarisation and circular polarisation Liquid crystal displays (LCD): a single pixel display Liquid crystals: quiz